A comparison of measured and predicted diffusion coefficients applied to sand and silt sized acid mine drainage materials. (1st February 2019) - Dettrick, D.; Costelloe, J.; Arora, M.; Yuen, S.
Abstract: Determining the rate at which Acid Mine Drainage (AMD) sulfide oxidation occurs in mining waste products is a central requirement for safe and sustainable long term design of storages, including tails storage facilities, ore stockpiles and waste rock dumps. Inappropriate design can result in AMD acidification, mobilisation of heavy metals and pollution of ground and surface waters. The use of soil gas (oxygen) transport modelling to model AMD based sulfide oxidation and potential acidity loads is widespread, but diffusion coefficients used for modelling are based on existing diffusion coefficient models derived for natural and agricultural soils. Mining wastes are often well sorted due to mineral processing, and differences in soil structure and porosity can impact on diffusion coefficient behaviour compared to natural soils. This study compares a variety of approaches to estimate the diffusion coefficient and compare these results to measured values for comparison and analysis. A diffusion column apparatus is used to compare diffusion coefficient models from the literature with test results from the laboratory in several mining derived AMD materials. The results of the comparison indicate that laboratory testing of diffusion provides more accurate estimation of soil gas diffusion coefficients in mine materials. The use of diffusion coefficient safety factor approaches are explored as possible alternatives, if measurement of mine material matrix soil gas diffusion coefficient is not possible. Highlights: Modelled diffusion coefficient data was compared with measured data for AMD soils. Mining wastes are strongly sorted in comparison to natural agricultural soils. Underestimates of diffusion may create AMD treatment problems. Diffusion coefficient safety factors are recommended if measurement is not possible. Design of economic < 500 diffusion chamber for mining sector using UPVC.